Steering unit cell dipole and internal electric field by highly dispersed Er atoms embedded into NiO for efficient CO₂ photoreduction - Yu, Zhenzhen (2022)
The weak internal electric field over antiferromagnetic materials makes it difficult to facilitate charge migration to the surface, leading to low performance for CO2 photoreduction. The asymmetry and polarization refinement structure can induce an intensive internal electric field. Herein, n-type NiO is synthesized with highly dispersed erbium atoms doping (Er/NiO1−x) via a molten salt method to accelerate charge separation and transfer. The doping of Er atoms can distort the unit cell of NiO to alter the symmetry and enhance the polarization and internal electric field, in favor of efficient separation of charges. In addition, the highly dispersed erbium-doped n-type NiO can largely boost the adsorption and activation of CO2, and weaken the energy barrier for CO2 photoreduction reaction. Benefiting from the unique features, an optimal doping ratio (≈2%) with erbium atoms achieves a remarkable elevation in carrier separation efficiency and excellent CO2 photoreduction performance with a CO yield of 368 µmol g−1 h−1 in the Ru(byp)32+/ethanolamine electron-agent generating system, which is 26.3-fold and 3.9-fold relative to traditional NiO and n-type NiO, respectively. The obtained Er/NiO1−x photocatalyst and the unit cell dipole governing the internal electric field opens a new window for CO2 photoreduction in antiferromagnetic materials.